Evidence-Based Nursing Practice dengan Mobilisasi Dini Berdasarkan Teori Defisit Perawatan Diri Orem pada Pasien Stroke Iskemik: Studi Kasus: Evidence-Based Nursing Care with Early Mobilization Based on Orem’s Self-Care Deficit Theory in an Ischemic Stroke Patient: A Case Study - Kurnia, Gian M; Agusni, Wulan; Susilawati, Susilawati; Hamami, Ayatullah (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Ischemic’ stroke is a leading cause of disability and mortality worldwide, particularly among older adults, and requires comprehensive, evidence-based management. Nursing care plays a crucial role in optimizing cerebral perfusion, preventing complications, and promoting functional recovery. This case study aims to describe the implementation of comprehensive nursing care using an Evidence-Based Nursing (EBN) approach integrated with Dorothea Orem’s Self-Care Deficit Nursing Theory in a patient with ischemic stroke.Smoking among adolescents remains a major public health concern in Indonesia. One preventive strategy is to enhance students’ self-efficacy to resist peer pressure to smoke. Health education is believed to improve self-efficacy, yet its effectiveness requires further empirical validation. A'descriptive case study was conducted on a 67-year-old female patient diagnosed with ischemic stroke and admitted to an inpatient ward. Comprehensive nursing assessment included neurological, hemodynamic, respiratory, nutritional, mobility, and self-care status. Assessment instruments used were the Glasgow Coma Scale (GCS), National Institutes of Health Stroke Scale (NIHSS), and Barthel Index. Nursing diagnoses were established based on the Indonesian Nursing Diagnosis Standards (SDKI), while interventions and outcomes were planned using the Indonesian Nursing Intervention Standards (SIKI) and Indonesian Nursing Outcome Standards (SLKI). The'main nursing diagnoses identified were decreased intracranial adaptive capacity, impaired gas exchange, decreased cardiac output, impaired physical mobility, and nonadherence to the therapeutic regimen. Evidence-based nursing interventions included intracranial pressure management, oxygen therapy, early post-stroke mobilization, self-care support, medication adherence education, and family involvement. Evaluation showed improvement in the patient’s level of consciousness, stabilization of vital signs, reduced headache intensity, increased muscle strength, and enhanced functional independence. NIHSS scores improved from moderate to mild neurological deficit, and the Barthel Index increased from severe to moderate dependency.